CONVERSATIONAL IMPLICATURE IN “CENTRAL INTELLIGENCE” MOVIE - Julio Agsa; Ambalegin Ambalegin (Asosiasi dosen IDEBAHASA KEPRI, 2022)
This descriptive qualitative research investigated conversational implicature found in the movie entitled “Central Intelligence”. The gricean theory was applied to examine the conversational implicature types uttered by characters of the “Central Intelligence” movie. The data were utterances of all characters involved in the movie. Conversational implicature was taken as the research object. Observational method and non-participatory were used to collect data. The pragmatic identity method and competence- in equalizing technique were adopted to analyze the collected data. Therefore, the researchers analyzed in a pragmatics way and equalized the data with theory. Relating to the findings, this research discovered the types of conversational implicature, namely particularized conversational implicature with 10 data, generalized conversational implicature with nine in which five data for scalar, and four data for indefinite. This research also discovered that particularized conversational implicature was the dominant type. The reason is that utterances in the movie needed a particular context to get the unstated meaning.